Transcriptome and Zymogram Analyses Reveal a Cellobiose-Dose Related Reciprocal Regulatory Effect on Cellulase Synthesis in Cellulosilyticum ruminicola H1 - Li, Shanzhen; Shao, Nana; Luo, Yuanming; Liu, Hongcan; Cai, Shichun; Dong, Xiuzhu (Frontiers in Microbiology, 2017)
The rumen bacterium Cellulosilyticum ruminicola H1 efficiently hydrolyzes cellulose. To gain insights into the regulatory mechanisms of cellulase synthesis, comparative transcriptome analysis was conducted for cultures grown on 2% filter paper, 0.5% and 0.05% cellobiose, and 0.5% birchwood xylan. It was found that cellulose induced a majority of (hemi)cellulases, including 33 cellulases and a cellulosomal scaffoldin (1.3 to 22.7-fold); seven endoxylanases, two mannanases, and two pectatelyases (2 to 16-fold); and pyruvate formate-lyase (PFL, 1.5 to 7 folds). Noticeably, 3- and 2.5-fold increased transcription of a cellobiohydrolase and the cellulosomal scaffoldin precursor were detected in 0.05% than in 0.5% cellobiose. Consistently, 9- and 4-fold higher specific cellobiohydrolase activities were detected in the filter paper and 0.05% cellobiose culture. SDS- and native-PAGE zymograms of cellulose-enriched proteins from the filter paper culture displayed cellulase activities, and cellulolytic “complexes” were enriched from the filter paper- and 0.05% cellobiose-cultures, but not from the 0.5% cellobiose culture. LC-MS/MS identified the cellulosomal scaffoldin precursor in the “complexes” in addition to cellulase, hemicellulase, and PFL proteins. The addition of 0.5% cellobiose, but not 0.05% cellobiose remarkably inhibited strain H1 to degrade filter paper. Therefore, this work reveals a cellobiose-dose related regulatory mechanism of cellulase synthesis by lower for induction and higher for repression, which has extended our understanding of the regulation of microbial cellulase synthesis.